Optimalisasi Akuntabilitas dan Transparansi: Pendekatan Islam pada Pedoman Asistensi Keuangan Desa Sikapas - Ardilla Nasution; Nurwani Nurwani; Laylan Syafina (Jurnal Akademi Akuntansi, 2024)
Purpose: The objective of this study is to evaluate the implementation of financial accounting assistance guidelines in Sikapas Village within the context of Islamic perspectives on transparency and accountability of village funds. Methodology/approach: This research is qualitative, utilizing primary data obtained through observations and interviews with various stakeholders in Sikapas Village, including the village treasurer, village head, secretary, and three other community members. Findings: The conclusion of the research shows that the financial assistance guidelines in Sikapas Village have not been fully implemented. This can be seen from the lack of understanding among village officials in applying the assistance guidelines, leading to delays in financial reporting. Additionally, village officials should possess four qualities of good leadership: siddiq, amanah, tabligh, and fatanah. Practical and Theoretical contribution/Originality: This research contributes to the literature in accounting, particularly in public sector accounting regarding transparency of village funds. Research Limitation: The researcher faced challenges in gathering data on accountability and transparency of financial reports in the remote village under study due to limited online publications, especially regarding total assets, income, and annual expenditures. Additionally, difficulties in obtaining reports on Village Budgets (APBD), information on Infrastructure Development Cost Estimates (RAB), and related data were also limitations in this study.